Food insecurity and its associated factors among lactating mothers in the Chiro district, Eastern Ethiopia: A community-based cross-sectional study - Minas, Selamu; Ayele, Behailu Hawulte; Sisay, Mekonnen; Tusa, Biruk Shalmeno; Roba, Kedir Teji (Frontiers in Nutrition, 2022)
Introduction Lactating mothers are extremely vulnerable to both macro and micronutrient deficiencies due to the increased nutritional requirements and high magnitude of food insecurity in low-income countries. However, there are a dearth of studies conducted in sub-Saharan African countries regarding this study area. Thus, this study aimed to assess the magnitude of food insecurity and its associated factors among lactating mothers in the Chiro district, eastern Ethiopia. Methods A community-based cross-sectional study was conducted among 446 randomly selected lactating mothers from 1–30 June, 2020. Data were collected through face-to-face interviews using a structured and pre-tested questionnaire. Data were entered using EpiData version 3.1 and exported to STATA version 14.2 for cleaning and analysis. Bi-variable and multivariable binary logistic regression analyses were fitted to check the association between independent variables and food insecurity. The level of statistical significance was declared at a p-value < 0.05. Results The magnitude of food insecurity among lactating mothers was 68.8 % (95 % CI: 64.4, 72.9) and 12.1% (95 % CI: 9.4, 15.5) were severely food insecure. Residing in the rural (AOR =2.36, 95% CI:1.21, 4.62), poor wealth indices (AOR =4.68, 95% CI:2.02, 10.8), owning farmland of less than a hectare (AOR =2.35, 95% CI:1.06, 5.19), mothers who had less than three meals a day (AOR =2.70, 95% CI:1.33, 5.46), and who did not have their own income (AOR =2.32, 95% CI:1.36, 3.96) were significantly associated factors with food insecurity among lactating mothers. Conclusion Food insecurity is highly prevalent in lactating mothers' households. Therefore, the government and other stakeholders need to take action that addresses factors affecting mothers' food security status through strengthening nutrition-sensitive interventions.